2014
DOI: 10.1177/0038040714547770
|View full text |Cite
|
Sign up to set email alerts
|

The High School Environment and the Gender Gap in Science and Engineering

Abstract: Despite the striking reversal of the gender gap in education, women pursue science, technology, engineering, and mathematics (STEM) degrees at much lower rates than those of their male peers. This study extends existing explanations for these gender differences and examines the role of the high school context for plans to major in STEM fields. Building on recent gender theories, we argue that widely shared and hegemonic gender beliefs manifest differently across schools so that the gender-specific formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(176 citation statements)
references
References 51 publications
11
161
0
4
Order By: Relevance
“…For example, knowledge (or even rumors) of discrimination in male-dominated science and engineering fields may influence occupational aspirations, leading some girls and women to forego STEM training and thereby reducing their future competitiveness in these fields. STEM avoidance by a few girls can have multiplier effects because adolescents respond strongly to standards set by same-gendered peers (Legewie and DiPrete 2014). Discriminatory treatment is also reinforced by behavioral responses to unbalanced gender ratios.…”
Section: Micro-level Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, knowledge (or even rumors) of discrimination in male-dominated science and engineering fields may influence occupational aspirations, leading some girls and women to forego STEM training and thereby reducing their future competitiveness in these fields. STEM avoidance by a few girls can have multiplier effects because adolescents respond strongly to standards set by same-gendered peers (Legewie and DiPrete 2014). Discriminatory treatment is also reinforced by behavioral responses to unbalanced gender ratios.…”
Section: Micro-level Explanationsmentioning
confidence: 99%
“…Although such policies would seem to be at odds with American ideals of individual choice and self-expression, research suggests that they might also weaken penetration of gender stereotypes and reduce peer pressure in course taking. Comparative studies show that the gender gap in STEM aspirations and outcomes tends to be smaller in countries and schools where curricular choice is reduced or delayed and where high school science and mathematics curricula are stronger (Federman 2007;Charles and Bradley 2009;Cheryan et al 2009;Legewie and DiPrete 2014;Scheeren et al 2018). This may be because reluctance to transgress gender norms declines with age (Gerson 1985;Jacobs 1989), or because exposing students to a broader array of fields provides them with better information about what they like and what they are good at.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Furthermore, and adding to previous research (Legewie and DiPrete, 2014a), our study suggests that in order to equalize the distribution of women and men across majors, interventions directed at adolescents' experiences during high school, when gender-specific substantive preferences are shaped and traditionalist peer norms form, are the most promising.…”
Section: Resultsmentioning
confidence: 55%
“…Although this distinction has been criticized (Charles and Grusky, 2004), distinguishing between behavioral differences that stem from differences in preferences and differences in constraints individuals face (Gambetta 1987;Zeng and Xie, 2008) is key for informing policy about whether to direct efforts towards schools and the way they shape aspirations (Legewie and DiPrete, 2014a) or instead towards removing constraints women face in the labor market (Reskin and Roos, 1990;Goldin, 2014). Distinguishing between preferences and constraints also renders our study informative for interpreting the large number of studies on gender wage gaps that decompose gender differences into 'explained' and 'unexplained' parts where authors routinely interpret results under the assumption that the explained part was more acceptable than the residual part, from a normative perspective (Blau and Kahn, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Girls did not have the same anti-school peer culture in low-SES schools, and for them the effect of school environment on performance was weaker. Legewie and DiPrete (2014) further explored school effects on the gender differences in the probability of continuing education after high school in a STEM subject and found that the gender gap in college application for a STEM subject is associated with a high school's curriculum in STEM and gender segregation of extracurricular activities. A recent study of Israeli schools (Cahan et al, 2014) also showed that school quality correlates with the gender gap in achievement: that is, in better schools boys tend to do comparatively better.…”
Section: Literature Reviewmentioning
confidence: 99%